Answer: equation of the tangent plane is z = 1
Step-by-step explanation:
Given equation
z = e^(-x²-y²) at point (0,0,1)
now let z = f(x,y)
Δf(x,y) = [ fx, fy ]
= (-2xe^(-x²-y²)), (-2ye^(-x²-y²))
now
Δf (0,0) = [ 0, 0 ] = [ a, b ]
equation of the tangent plane therefore will be
z - z₀ = a(x-x₀) + b(y-y₀)
z - 1 = 0(x-0) + 0(y-0)
z - 1 = 0 + 0
z = 1
Therefore equation of the tangent plane is z = 1
Answer:
I had same one so the answer is C
Step-by-step explanation:
♦I hope this helps you also please mark brainliest ♦
♦☻☺Thanks☺☻♦
Answer:
D. y = –2x – 7
Step-by-step explanation:
First, find the <em>rate</em><em> </em><em>of change</em><em> </em>[<em>slope</em>]:
-y₁ + y₂\-x₁ + x₂ = m
In this case, the y-intercept of [0, -7] is ALREADY given to you, so we would not have to go further in this case.
I am joyous to assist you anytime.
The ratio of the shortest sides is 12/5. Multiplying the other two sides of the smaller triangle by that ratio gives 15 and 18, so the ratios of all sides are the same. The triangles are similar.
ABC ~ ZYX
The largest/smallest scale factor is 12/5 = 2.4.
Step-by-step explanation:
tanB + cotB = (sinB)/(cosB) + (cosB)/(sinB)
= (sin2B + cos2B)/[(cosB)(sinB)]
= 1/[(cosB)(sinB)]
= (1/cosB)(1/sinB)
= (secB)(cscB)